Leaflet anatomy of Poiretia Vent. (Leguminosae, Papilionoideae, Dalbergieae) with emphasis on internal secretory structures in support of taxonomy - Mendes, Katiane Reis [UNESP]; Fortuna-Perez, Ana Paula [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Elsevier, 2019)
Poiretia Vent. is a Leguminosae (Papilionoideae, Dalbergieae) genus comprising 12 species which are distinguished mainly by external morphology of the leaves and inflorescences; however, overlapping in variation of several morphological traits has led to taxonomic problems, including erroneous identifications of species and varieties. Furthermore, attributes of recognized importance among legumes, such as characteristics of secretory structures, have been neglected in the distinction of Poiretia species. Here we described the leaflet blade anatomy of all 12 Poiretia species emphasizing the internal secretory structures in order to identify characters with potential taxonomic value. Leaflets were obtained from herbarium and from plants occurring in natural environments. Samples were processed according to standard techniques for plant anatomy. The leaflets of P. angustifolia and P. punctata were hypostomatic, whereas those of the other species were amphistomatic. The adaxial face of the main vein was flat in P. bahiana, P. coriifolia, P. latifolia and P. unifoliolata, slightly convex in P. elegans and concave in the other species. Bundle sheath extensions were observed in eight of the 12 species. A fiber cap with lignified walls was present externally to the phloem of the midrib, except P. bahiana, P. latifolia, P. marginata and P. punctata. Secretory cavities were present in the mesophyll of all species; in P. angustifolia, P. latifolia, P. longipes, P. marginata and P. tetraphylla secretory cavities occurred in the region of the mesophyll near the midrib, while in P. latifolia the secretory cavities occurred in the cortex of the midrib. The number of epithelial layers varied among species, with secretory cavities having two to six cell layers. Idioblasts in the epidermis of P. crenata, P. latifolia and P. mattogrossensis were quite voluminous. The distinctive characteristics observed among the species were used to develop an identification key for the species of Poiretia.
Keywords: Idioblasts; Leaflet blade; Plant systematics; Secretory cavities; Stomata; Vein